2012
DOI: 10.1007/s13353-012-0129-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of IGF1 and KDM5A polymorphisms with performance, fatness and carcass traits in chickens

Abstract: Two functional and positional candidate genes were selected in a region of chicken chromosome 1 (GGA1), based on their biological roles, and also where several quantitative trait loci (QTL) have been mapped and associated with performance, fatness and carcass traits in chickens. The insulin-like growth factor 1 (IGF1) gene has been associated with several physiological functions related to growth. The lysine (K)-specific demethylase 5A (KDM5A) gene participates in the epigenetic regulation of genes involved wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 31 publications
0
36
0
3
Order By: Relevance
“…These markers have been previously associated with QTL for tibia plateau angle (Sharman et al, 2007) and femur bone mineral density (Rubin et al, 2007). In this same region, two candidate genes associated with performance traits, fat deposition and carcass percentage are mapped: insulin-like growth factor 1 (IGF1) and lysine (K)-specific demethylase 5A (KDM5A) (Boschiero et al, 2013). Sharman et al (2007) also mapped QTL for tibia weight on GGA1, in the region flanked by markers MCW0297 and LEI0146.…”
Section: Quantitative Trait Loci Mappingmentioning
confidence: 97%
“…These markers have been previously associated with QTL for tibia plateau angle (Sharman et al, 2007) and femur bone mineral density (Rubin et al, 2007). In this same region, two candidate genes associated with performance traits, fat deposition and carcass percentage are mapped: insulin-like growth factor 1 (IGF1) and lysine (K)-specific demethylase 5A (KDM5A) (Boschiero et al, 2013). Sharman et al (2007) also mapped QTL for tibia weight on GGA1, in the region flanked by markers MCW0297 and LEI0146.…”
Section: Quantitative Trait Loci Mappingmentioning
confidence: 97%
“…For better understanding of complex traits control in a segregating F2 population, our research group have focused the attention on genetic association and linkage analyses using different approaches, as: candidate genes (BOSCHIERO et al, 2013;FELÍCIO et al, 2013aFELÍCIO et al, , 2013bPÉRTILLE et al, 2015) and QTL mapping (NONES et al, 2006(NONES et al, , 2012AMBO et al, 2008AMBO et al, , 2009CAMPOS et al, 2009), respectively, and more recently, NGS approaches (GODOY et al, 2015;MOREIRA et al, 2015). We have presented here the first study using a higher density of SNPs in this F2 population with GWAS purpose.…”
Section: Discussionmentioning
confidence: 99%
“…This small effect also was previously Also is important to check if these SNPs are within QTL regions previously published. In the past years, many studies identified QTLs associated with performance traits in different chickens populations (TATSUDA;FUJINAKA, 2001;KONING et al, 2003;IKEOBI et al, 2004;ZHOU et al, 2006;NONES et al, 2006NONES et al, , 2012AMBO et al, 2008AMBO et al, , 2009BOSCHIERO et al, 2013;NASSAR;GORAGA;BROCKMANN, 2012BROCKMANN, , 2013 (1,458 QTLs described in the Animal QTLdb) aiming to map loci that control these traits. Recently, to better understand these loci, studies have also applied GWAS with performance traits in chickens (ZHOU et al, 2006;GU et al, 2011;XIE et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations